2023
DOI: 10.1002/ep.14097
|View full text |Cite
|
Sign up to set email alerts
|

Financing green and climate resilient infrastructure in ASEAN countries

Abstract: Southeast Asia is one of the world's most energy-intensive and climate vulnerable regions, with rapid urbanization and industrialization increasing its greenhouse gas emissions and a high exposure to extreme weather events. The COVID-19 pandemic has had a massive impact on the region's economic growth. Decisions taken by leaders today to revive economies will either entrench the region's dependence on fossil fuels or accelerate decarbonization efforts to achieve the Paris Agreement and the Sustainable Developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…This result is confirmed by Ref. 4 , 52 , 69 who revealed that the Global Climate Fund (GCF) approved an investment portfolio of $795 million in 2021 to support the region’s investment efforts. In addition, the GCF ASEAN Catalytic Green Finance Facility (ACGF) was recently implemented by the Asian Development Bank, which is a public–private co-investment initiative designed to simultaneously support a broad portfolio of green infrastructure to achieve sustainable development and to enable an inclusive economic recovery in the Southeast region.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…This result is confirmed by Ref. 4 , 52 , 69 who revealed that the Global Climate Fund (GCF) approved an investment portfolio of $795 million in 2021 to support the region’s investment efforts. In addition, the GCF ASEAN Catalytic Green Finance Facility (ACGF) was recently implemented by the Asian Development Bank, which is a public–private co-investment initiative designed to simultaneously support a broad portfolio of green infrastructure to achieve sustainable development and to enable an inclusive economic recovery in the Southeast region.…”
Section: Resultsmentioning
confidence: 61%
“…On the other hand, public financing is the situation in that development projects are explicitly or implicitly funded by the government, thereby affecting the liability of the state 51 . From 2010 and 2021, debt and equity investments were made up of 47% and 48% of cumulative financing, with an extra 5% contribution from grants 52 . The study further noted that equity finance was mainly used to finance company expansion and growth.…”
Section: Literature Reviewmentioning
confidence: 99%